The Prevalence of Ptosis and Its Association with Amblyopia and Strabismus in 7-Year-Old Schoolchildren in Iran. (3rd July 2015) - Hashemi, Hassan; Nabovati, Payam; Dadbin, Nooshin; Heidari, Zahra; Yekta, AbbasAli; Jafarzadehpur, Ebrahim; Ostadimoghaddam, Hadi; Khabazkhoob, Mehdi
Abstract: Purpose : To determine the prevalence of ptosis (congenital/acquired) in Iranian children aged 7 years and its relationship with amblyopia and strabismus. Methods : Eight Iranian cities were selected for this cross-sectional study using multistage randomized cluster sampling. A number of primary schools were randomly selected in each city. All grade 1 students in each selected primary school underwent optometric examinations including the measurement of uncorrected and corrected visual acuity, cover test, and cycloplegic and non-cycloplegic refraction. Results : Of 4614 selected students, 4106 students participated in the study (response rate = 89%). The prevalence of ptosis (congenital/acquired) was 1.41% (95% CI 1–1.83); 0.49% (95% CI 0.26–0.72) and 0.93% (95% CI 0.59–1.26) had unilateral and bilateral ptosis, respectively. The prevalence of ptosis had no significant correlation with sex ( p  = 0.810, OR = 1.07, 95% CI 0.59–1.97). The prevalence of amblyopia was 48.28% and 0.89% in students with and without ptosis, respectively. The prevalence of tropia was significantly higher in cases with bilateral ptosis ( p  < 0.001). The mean cylinder error was 1.63 ± 1.72 and 0.44 ± 0.60 in ptotic and non-ptotic eyes, respectively ( p  < 0.001). With-the-rule (WTR) astigmatism was significantly more prevalent in students with ptosis. Conclusion : We report the prevalence of ptosis (congenital/acquired) in children in Iran and the Middle East region for the first time. Amblyopia was considerably more prevalent in ptotic patients. We found a significant correlation between ptosis and tropia. Astigmatism, especially WTR stigmatism, was more prevalent in children with ptosis.